NUTRITIONAL STATUS OF ADOLESCENTS OF DANKANDE COMMUNITY OF KADUNA METROPOLIS (FUDMA JOURNAL OF SCIENCES, 2021)
Studies on the nutritional status of adolescents in Dankande community of Kaduna metropolis were carried out. Adolescence is a period between 10 to 19 years of age. This period is a critical period where a healthy diet is needed for proper growth, development, academic performances and human capital development. A validated semi-structured questionnaire was used to assessed socio-demographic characteristic of the adolescent caregivers and dietary pattern of the adolescent while weight, height and BMI were used to assess the anthropometry indices of adolescent. 37.2% of adolescents were between age 10-14 years while 62.8% were between 15-19 years. Also, 5.1% of the adolescents were married, 88.5 were single and 6.4% windowed. (19.2%) of adolescents has no formal education, (2.6%) completed primary school, (29.5%) uncompleted primary school, (2.6%) completed Junior Secondary School, (19.2%) uncompleted Junior Secondary School, while (1.3%) completed Senior Secondary and (25.6%) did not complete Senior Secondary respectively.However, on average (35.9%) of adolescent were dieting and (64.1%) were not dieting while (32.1%) were concerned about their weight and (67.9%) were not concerned about their weight. Few adolescents were losing control of their weight (24.4%) while the majority had their weight in check (75.6%), they engaged in physical activity (85.9%), while many adolescents spent more than two hours per day watching tv/games (69.2%).  17.9% engage in smoking while (5.1%) are involved in drinking alcohol, beer or wine. The nutritional status of adolescents of Dankande community of Kaduna state (56.4%) is good when compared with the national average
Keywords: Kaduna, Dankande, Adolescents, Nutritional status